Genetic Variation in Antioxidant Enzymes, Cigarette Smoking and Longitudinal Change in Lung Function - Tang, W (2013)
RATIONALE: Antioxidant enzymes play an important role in the defense against oxidative stress in the lung and in the pathogenesis of chronic obstructive pulmonary disease (COPD). Sequence variation in genes encoding antioxidant enzymes may alter susceptibility to COPD by affecting longitudinal change in lung function in adults. METHODS: We genotyped 384 sequence variants in 56 candidate genes in 1,281 African-American and 1,794 European-American elderly adults of the Health, Aging, and Body Composition study. Single-marker associations and gene-by-smoking interactions with rate of change in FEV(1) and FEV(1)/ FVC were evaluated using linear mixed effects models, stratified by race/ethnicity. RESULTS: In European-Americans, rs17883901 in GCLC was statistically significantly associated with rate of change in FEV(1)/FVC; the recessive genotype (TT) was associated with a 0.9% per year steeper decline (P = 4.50 × 10(−5)). Statistically significant gene-by-smoking interactions were observed for variants in two genes in European-Americans: the minor allele of rs2297765 in mGST3 attenuated the accelerated decline in FEV(1)/FVC in smokers by 0.45% per year (P = 1.13 × 10(−4)); for participants with greater baseline smoking pack-years, the minor allele of rs2073192 in IDH3B was associated with an accelerated decline in FEV(1)/FVC (P = 2.10 × 10(−4)). For both genes, nominally significant interactions (P < 0.01) were observed at the gene-level in African-Americans (P = 0.007 and 4.60 × 10(−4), respectively). Nominally significant evidence of association was observed for variants in SOD3 and GLRX2 in multiple analyses. CONCLUSIONS: This study identifies two novel genes associated with longitudinal lung function phenotypes in both African- and European-Americans, and confirms a prior finding for GCLC. These findings suggest novel mechanisms and molecular targets for future research and advance the understanding of genetic determinants of lung function and COPD risk.